Density control method for compression test of compacted lime-flyash stabilised fiber-soil mixtures - Kafodya, Innocent; Okonta, F (MethodsX, 2018)
[Display omitted] The unconfined compressive strength test is the widely accepted protocol to investigate the strength properties of lime amended soil. As a quality control measure, specimens for unconfined compression test are prepared at a predetermined maximum dry density (MDD) using standard Proctor test. Replicating MDD in a small sized mould is difficult and subject to errors, which normally arise due to inconsistent compaction efforts. The conventional method for preparing specimens involves driving a core sampler into the compacted soil to extract the specimen. The approach proves to be laborious and is associated with high material usage, as such is not ideal for investigations of many variables. To address these challenges, an alternative protocol for specimen preparation at a controlled dry density was devised. In this study, a statistical analysis of the density values was used to validate the method. The regression analysis was employed to calibrate the compaction effort for a specified target density. The method offers manifold benefits such as; •Improved quality of specimens.•Reduced variability of UCS test data.•Efficiency.•Reduced material usage.